Superalloys 718, 625, 706 and Various Derivatives (2001) 2001
DOI: 10.7449/2001/superalloys_2001_149_160
|View full text |Cite
|
Sign up to set email alerts
|

The Tendency for Freckle Formation in Alloy 718

Abstract: Solidification macro-segregation, particularly in the form of freckles, in nickel base superalloys is the main cause for the limitation of the ingot diameter and melting rate during vacuum arc remelting (VAR) and electro-slag remelting (ESR) process.The critical solidification conditions for freckle formation in Alloy 71 8 were studied by horizontal directional solidification (H-DS) experiments under various solidification conditions, and validated by commercial sized VAR ingots. The tendency for freckle forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It is suggested that the initiation of freckle channel formation is the result of local irregularities in the dendrite network which lead to local increases in the network permeability. The random nature of the irregularities accounts for the formation of a small number of freckles in an ingot with no indicated regions of high Ra number [18]; also for the demonstrated possibility of producing an ingot without freckles under process parameters which would produce a high Ra value in the ingot [17]. The irregularities are the result of perturbations in the heat balance of the solidifying dendritic front brought about principally by lack of control of the arc heating process.…”
Section: Irregularities In the Var Processmentioning
confidence: 99%
“…It is suggested that the initiation of freckle channel formation is the result of local irregularities in the dendrite network which lead to local increases in the network permeability. The random nature of the irregularities accounts for the formation of a small number of freckles in an ingot with no indicated regions of high Ra number [18]; also for the demonstrated possibility of producing an ingot without freckles under process parameters which would produce a high Ra value in the ingot [17]. The irregularities are the result of perturbations in the heat balance of the solidifying dendritic front brought about principally by lack of control of the arc heating process.…”
Section: Irregularities In the Var Processmentioning
confidence: 99%
“…However, freckle type defects have also been observed for alloy 718 in industrial castings [12,20,[27][28][29], although heavy elements like Nb lead to an increasing density of the segregated melt during solidification of this alloy which should result in the formation of a stable layering. Similar to buoyancy driven freckles, these defects appear as dark spots in the cross-section, preferentially at mid-radius of the ingot.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of density inversion for alloy 718 was either ignored [20,31] or rejected, pointing out that the high silicon contents of older grades of alloy 718 could have led to a decreasing density of the melt during solidification [12,27,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation